The Influence of Taxpayer Knowledge and Taxpayer's Awareness On Land and Building Taxpayer Compliance: Study in One of the District in Bandung District - Wajib Ginting (Acman: Accounting and Management Journal, 2022)
This study investigates the effect of taxpayer knowledge and taxpayer awareness on taxpayer compliance with Land and Building Tax. The research method uses a survey approach to taxpayers in one of the sub-districts in Bandung Regency. The number of respondents who are willing to fill out the questionnaire is 100 taxpayers. The results of the study indicate that there is an influence of taxpayer knowledge and taxpayer awareness on taxpayer compliance with Land and Building Tax. The results of the study recommend that the government provide socialization regarding the important role of land and building tax in order to increase taxpayer compliance in paying land and building tax.